Searches for Anisotropies in the Arrival Directions of the Highest Energy Cosmic Rays Detected by the Pierre Auger Observatory - Almela, Daniel Alejandro; Purrello, Víctor Hugo; Asorey, Hernán Gonzalo; Bertou, Xavier Pierre Louis; Dasso, Sergio Ricardo; Dova, Maria Teresa; Etchegoyen, Alberto; Figueira, Juan Manuel; Filevich, Alberto; Garcia, Beatriz Elena; Gomez Berisso, Mariano; Hansen , Patricia Maria; et al. (Iop Publishing, 2015)
Fil: Almela, Daniel Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Tecnologías en Detección y Astropartículas; Argentina